The determinants of rural migrants' employment choice in China: Results from a joint estimation - Yuling Cui; Daehoon Nahm; Massimiliano Tani (Institute for the Study of Labor (IZA), 2012)
This paper investigates the determinants of employment choice of rural migrant workers across state-owned enterprises (SOEs) and various subtypes of non-state owned enterprises (non-SOEs) by taking into account unobservable characteristics that link the choice to migrate with the choice of employer. Using pooled cross-section data for 1995 and 2002, the results indicate that the choice of employment is positively related to unobserved determinants of migration. This result implies that estimating employment choices without controlling for migration status leads to biased estimates. Most rural migrants appear strongly pulled into non-SOEs because of the higher wages and despite longer working hours. The provision of pension benefits also positively motivates employees' choices.
Keywords: C35; J21; J61; 330; rural migrant workers; employment choice; SOEs; non-SOEs; China; Landflucht; Regionale Arbeitsmobilität; Arbeitsuche; Öffentliches Unternehmen; Privatwirtschaft; China